Trust As Mediator Between Service Quality And Customer Satisfaction: Evidence From Courier Services In Surabaya And Sidoarjo - Fardan, Moch Khoirul Fardan; Rachma Rizqina Mardhotillah; Azmil Chusnaini; Reizano Amri Rasyid (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
This study examines the effect of service quality on customer satisfaction with trust as a mediating variable, focusing on JNE courier service customers in Surabaya and Sidoarjo. Employing a quantitative research design, data were collected through questionnaires distributed to 121 respondents and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings reveal that both service quality and trust have a positive and significant influence on customer satisfaction; however, trust does not significantly mediate the relationship between service quality and customer satisfaction. The study’s scope was limited to courier service customers in two major Indonesian cities, suggesting the need for future research to expand the sample size, include multiple courier firms, or conduct cross-regional comparisons to enhance external validity. These results emphasize the strategic importance for courier companies to improve service quality and strengthen customer satisfaction while fostering trust through transparent, consistent, and reliable service performance. This research contributes empirical evidence on the mediating role of trust within Indonesia’s courier service industry and enriches the growing literature on customer behavior and digital service management in emerging markets.